Uterine and Corpus Luteum Blood Flow Evaluation Prior to Uterine Flushing in Llama Embryo Donors - Zampini, Enzo G.; Gallelli, María F.; Chaves, María G.; Neild, Deborah M.; Gambarotta, Mariana; Miragaya, Marcelo H.; Trasorras, Virginia L. (Frontiers in Veterinary Science, 2020)
The aim of this study was to assess the uterine blood flow (UBF) and corpus luteum blood flow (CLBF) in llamas eight days post-mating, using color-Doppler ultrasonography (CDU), to determine the possible relationship between vascularization and the presence of an embryo. Adult females (n=25) were used to monitor ovarian dynamics by palpation and transrectal ultrasonography until detection of a ≥ 6 mm growing follicle. Females were randomly assigned to one of two groups: Group I (n=19), were mated and ovulation was induced by a single dose of buserelin (GnRH analogue) that same day (Day 0); and Group II (n=6), only ovulation was induced (control). On Day 8, UBF and CLBF were evaluated transrectally in both groups. The color-flow images obtained were analyzed with Image J1.52a software to determine the vascularization area and the percentage of corpus luteum with blood flow emission (CLBF%) together with the percentage for each uterine horn (UBF%). Statistical analysis was performed using an ANOVA test. In Group I, uterine flushing was performed to obtain the embryos, thus dividing the females into Group I+ (n=10), when an embryo was recovered and Group I- (n=9), when no embryo was recovered. Embryo recovery rate was 52.63% (10/19). In Group I+, UBF% was significantly higher compared to Group I- and Group II (P<0.05). UBF appears to be a good predictor for embryo presence, with an area under the curve (AUC) of 0.9 and an optimal cut-off value of 9.37% (with a sensitivity of 90% and specificity of 88.9%). The CLBF% did not differ between groups (P>0.05). In conclusion, it is possible to detect a local increase of UBF in the presence of an embryo on day 8 post-mating in llamas. This could be useful to achieve an early pregnancy diagnosis or to decide whether to carry out the uterine flushing in a llama embryo transfer program.